2016
DOI: 10.7717/peerj.1962
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with human saliva are major microbial components of Ecuadorian indigenous beers (chicha)

Abstract: Indigenous beers (chicha) are part of the indigenous culture in Ecuador. The fermentation process of these beers probably relies on microorganisms from fermented substrates, environment and human microbiota. We analyzed the microbiota of artisanal beers (including a type of beer produced after chewing boiled cassava) using bacterial culture and 16S ribosomal RNA (rRNA) gene-based tag-encoded FLX amplicon pyrosequencing (bTEFAP). Surprisingly, we found that Streptococcus salivarius and Streptococcus mutans (par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Future research should include such paired samples as well as samples from nonbakers to more directly test if bakers have unique, food-influenced microbiomes. Additional studies could test if bakers and chefs more generally colonize the food they make as has been shown with the traditional production of chicha, a fermented cassava drink (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include such paired samples as well as samples from nonbakers to more directly test if bakers have unique, food-influenced microbiomes. Additional studies could test if bakers and chefs more generally colonize the food they make as has been shown with the traditional production of chicha, a fermented cassava drink (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological and biochemical studies reported Lactobacillus and Leuconostoc genus as the main actors of the fermentation process [6,7]. More recently, molecular studies by next-generation sequencing (NGS) techniques revealed that lactic acid bacteria (LAB) and yeasts are the dominant populations responsible of the organoleptic traits of this beverage [8][9][10][11]. These data enlarged knowledge about the microbiota composition of this fermented product during the different steps of the manufacturing process, enabling the detection of minoritary species or of difficult-to-cultivate bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…These data enlarged knowledge about the microbiota composition of this fermented product during the different steps of the manufacturing process, enabling the detection of minoritary species or of difficult-to-cultivate bacteria. Although maize-based chicha is produced in the Northwestern Argentina [9,11], cassava chicha from Ecuador [10] and mais or rice-based Brazilian chicha [12,13] have been investigated, thus no data are available for Peruvian chicha, where this beverage is still very popular.…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, they were microbes associated with human or other mammal bodies. Modern examples of the latter include the use of salivary microbial communities to initiate the fermenting process in chicha production in Peru, and similar fermented beverages around the world (Freire et al, 2016), the use of skin microbes to produce bodily aromas in some semi-soft cheeses (Pham et al, 2017), the use of body associated Lactobacillus species in sourdough breads (Gänzle and Ripari, 2016) or the use of the ancestrally mouth-associated bacteria species, Streptococcus thermophilus, in the production of yogurt (Goh et al, 2011). Once they began using body and other microbes to ferment foods, our ancestors extended their genomes and ultimately their phenotypes in much the way that beavers do in building a dam that yields a pond (Carthey et al, 2018).…”
Section: The Extended Microbiomementioning
confidence: 99%